Application of A Joyful Learning Strategy Based on Humor Communication to Improve the Interests and Achievements of Learning English - Wahyuni Wahyuni; Muh. Rezky Naim (Universitas Sulawesi Barat, 2019)
Enhancing the quality of education in particular to improve the quality of students, a teacher must also improve their selves to delivering better learning innovations and one of those efforts by Using appropriate learning strategies so that the material delivered by the teacher can be young to be understood by students. The strategy in question is communicating with humor. The use of humor in the learning process is a medium for educators to students in transferring their knowledge because with humor can create better communication so that the classroom atmosphere is more comfortable. The purpose of this research had three important stages, including 1) to find out a lecture communication with students can be better so that through communication with humor can reduce the problem of lecturers with Students of which currently margined violence cases between lecturers and students, 2) increased achievement of learners learning because through humor communication through joy full learning students will learn more relaxed without any pressure so Easier to do tasks, 3) increased achievement and interest in students ' study in English courses as a General basic course. The method used in this research was the experimental Research design (quasi) method using the control class and experiment class. The study used three research instruments: interview, student observation (participant observation), student learning results. The results showed that there were differences in the pre-test and post-test values in experimental classes and the control class as well as the results of independent analysis of T-test result of Sig (2-tailed) 0.00 where the result of this value is smaller than 0.05. Indicates there is a significant difference between the Ecperimental and control classes in terms of application of the Stratei Learning Joyfull Learning-based humor to increase the interest and achievement of English learning as a public course in students STIE Yapman Majene.